2018
DOI: 10.1007/s00246-018-1892-x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Deformation of the Right Ventricle in Hypoplastic Left Heart Syndrome: A Comparative Study of 2D-Feature Tracking Magnetic Resonance Imaging and 2D-Speckle Tracking Echocardiography

Abstract: In hypoplastic left heart syndrome (HLHS), long-term outcome is closely related to right ventricular function. Echocardiography and magnetic resonance imaging (MRI) are routinely used for functional assessment. MRI 2D-tissue feature tracking (2D-FT) allows quantification of myocardial deformation but has not yet been applied to HLHS patients. We sought to investigate the feasibility of this technique and to compare the results to 2D-speckle tracking echocardiography (2D-STE). In routine MRI 2D anatomical four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
2
8
0
2
Order By: Relevance
“…We did not find any age-related difference of RVFW-GLS and systolic GLSR in neither gender groups and no correlation between age and RVFW-GLS or systolic GLSR. This finding was in line with the finding of previous studies [22,33,37]. This finding may simplify the establishment of reference values and clinical use of these two parameters.…”
Section: Gender-and Age-related Differences Of Rvfw-ls and Lsrsupporting
confidence: 92%
“…We did not find any age-related difference of RVFW-GLS and systolic GLSR in neither gender groups and no correlation between age and RVFW-GLS or systolic GLSR. This finding was in line with the finding of previous studies [22,33,37]. This finding may simplify the establishment of reference values and clinical use of these two parameters.…”
Section: Gender-and Age-related Differences Of Rvfw-ls and Lsrsupporting
confidence: 92%
“…Volume measurement is an essential parameter in the Previous studies demonstrated good agreement of conventional strains with CMRI in both functionally single LV (SLV) and SRV after Fontan palliation. 17, 18 Moreover, Satriano et al showed good correlation of not only CS and LS but also PS between 3D-STE and CMRI in the LV. 14 However, because PS is a very new concept, so far there have not been any studies demonstrating correlation of PS and CMRI in children.…”
Section: Discussionmentioning
confidence: 99%
“…The data analysis was performed using dedicated STE software (EchoPac, version 113, General Electric Healthcare, Wisconsin, USA) as previously described by our group. 15…”
Section: D-ste Analysismentioning
confidence: 99%
“…11,12 Beside traditional techniques, tissue tracking methods such as 2-dimensional (2D) CMR feature tracking (2D-CMR-FT) and 2D speckle tracking echocardiography (2D-STE) have gained popularity to assess global and regional myocardial deformation of the SV. [13][14][15] However, most studies have assessed a mixed cohort of single left (SLV) and single right ventricle (SRV) patients but only few assessed a uniform population of only SLV patients using 2D-STE. 16,17 A comparison to healthy controls was only performed in a small cohort in 2 studies.…”
Section: Introductionmentioning
confidence: 99%